Theories and antecedents of knowledge sharing behaviour in virtual community: A systematic review - Muhammad Ashraf, Fauzi; Nor Rokiah Hanum, Md Haron; Fatin Izzati, Ramli; Hamirahanim, Abdul Rahman; Zetty Ain, Kamaruzzaman (Amity School of Communication, 2020)
Virtual Community (VC) isregarded as the best platform for professionals in various fields to share their expertise and knowledge. Since the escalation of web 2.0 and the internet within the last decade and the booming interest in big data and expansion of industry 4.0, VC is deemed as an ideal proxy for practitioners to share and earned instant knowledge that can beimplemented within business activities and day to day application. Despite this emerging interest, there has been no comprehensive study on the overall antecedents of KS in VC. Applying a systematic review, a total of 68 relevant articles that discusses knowledge sharing (KS) via VC are evaluated. Several central themes of theories applied in this field within the literature are discussed on its importance and relevance. Important antecedents arealso reviewed on its practicality and implementation in understanding the role of KS in VC. The implication of this review would benefit stakeholders in maintaining the sustainability of VC as the platform for a knowledge-based society.